Strategi Peningkatan Penjualan Makanan Khas Kec. Dua Koto Kabupaten Pasaman - Asyhadi Diffa Pawira; Jon Kenedi (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This research is motivated by the low number of sales of typical food products in Dua Koto District, which is caused by the lack of promotion and innovation of products. The purpose of this research is to analyse the right strategy to increase product sales in the future. This research uses descriptive qualitative method with data collection techniques through observation, interviews, and SWOT analysis. The results showed that the most effective strategy is the ST strategy, which utilises existing strengths to overcome various threats that arise. This strategy includes increasing promotions, product innovation, and improving service quality to make products more competitive in the market. With the implementation of this strategy, it is expected that managers and sellers of typical food products can be more active in promoting their products, both through social media and direct marketing. In addition, innovations in packaging and product variations also need to be considered in order to attract more consumers. If this strategy is implemented optimally, it is expected that the number of sales of typical food products in Kecamatan Dua Koto will increase significantly in the future.